1995
DOI: 10.1063/1.115384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multiplication layer width on breakdown voltage in InP/InGaAs avalanche photodiode

Abstract: Breakdown voltages of InP/InGaAs avalanche photodiodes have been analyzed with structure parameters, such as multiplication layer width (MLW) and absorption layer thickness. It is shown that there exists a critical MLW, w0, where the breakdown voltage is the lowest. As MLW increases, the breakdown voltage increases slowly in the region of MLW≥w0 while the breakdown voltage decreases in the region of MLW≤w0. It is also revealed that w0 is a function of absorption layer thickness. The measured breakdown voltages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…These curves all show nonmonotonous dependence on the multiplication layer thickness, and a minimum is found at about 0.225 µm for the nominal multiplication layer thickness. This feature is qualitatively consistent with the simulation results based on traditional multiplication formula as reported by Itzler et al 33,35 and by Park et al 36 The explanation for this minimum could be referred to Fig. 2.…”
Section: Results Analyses and Discussionsupporting
confidence: 82%
“…These curves all show nonmonotonous dependence on the multiplication layer thickness, and a minimum is found at about 0.225 µm for the nominal multiplication layer thickness. This feature is qualitatively consistent with the simulation results based on traditional multiplication formula as reported by Itzler et al 33,35 and by Park et al 36 The explanation for this minimum could be referred to Fig. 2.…”
Section: Results Analyses and Discussionsupporting
confidence: 82%
“…We found that in our situation this process is more reliable and repeatable than double diffusion [13][14] and regrown metalorganic chemical vapor deposition (MOCVD) technique [7,16]. The epitaxial structure of planar InP/InGaAs APD was grown by MOCVD.…”
Section: Methodsmentioning
confidence: 98%
“…As seen in the solid curve in Fig. 4, there is a maximal value of the dark current when the multiplication thickness is 0.5µm, which may owe to the increasing of the gain at the same voltage [6], and then the dark current is reduced with the decreasing of the electric field.…”
Section: B Multiplication Layer Thicknessmentioning
confidence: 94%